TRUNCATED-POSITIONAL DECODING METHOD OF TRANSFORMANT BY NON-UNIFORMLY DIAGONAL FORMAT - Barannik, Vladimir; Shulgin, Sergii; Barannik, Dmitriy; Onyshchenko , Roman; Revva, K. (Science-based technologies, 2023)
The article shows that the level of criticality and relevance of video information, which is used to form decisions in critical and defense infrastructure systems, is increasing. A set of requirements for qualitative and quantitative indicators of video information interaction is dictated. These include the following: reliability; Fullness; integrity; timeliness (efficiency); confidentiality; Stealth. At the same time, there is a need to use wireless telecommunication technologies to ensure information exchange. At the same time, the productivity of such technologies is limited by a significant increase in the information intensity of video information flows. Therefore, there is an urgent scientific and applied problem that concerns the elimination of the imbalance between the productivity of telecommunication technologies and the level of information intensity of video streams. It is argued that the direction of elimination of this imbalance is the improvement and development of new methods of encoding information flows. Here, one of the approaches to improve video encoding technologies concerns the development of new concepts to reduce redundancy in segments and their transformed variants. The method of truncated-positional coding is considered. Based on the use of this method for encoding transformed video segments in an unevenly diagonal format, an additional increase in the compression level is achieved without introducing loss of integrity. This factor creates the potential for the integration of these technological solutions into a standardized video processing platform. Accordingly, conditions are provided to eliminate the imbalance between the level of reduction in the bit volume of video frames and their integrity. Hence, it is necessary to develop a method of truncated-positional decoding of transformants in an unevenly-diagonal format. A system of the decisive rule for determining the additive informative-positional weight, which includes the value of the current major element of the number, has been built. This rule is based on: a mathematical relationship for an approximate estimate of the code value of a number relative to its additive components by the highest element; positional basis properties that allow you to approximate the lower and upper limits of the code value change.